On the origin of the anomalous compliance of dealloying-derived nanoporous gold. (15th March 2017) - Ngô, B.-N. D.; Roschning, B.; Albe, K.; Weissmüller, J.; Markmann, J.
Abstract: The origin of the anomalously compliant behavior of nanoporous gold is studied by comparing the elasticity obtained from molecular dynamics (MD) and finite element method (FEM) simulations. Both models yield a compliance, which is much higher than the predictions of the Gibson-Ashby scaling relation for metal foams and thus confirm the influence of other microstructural features besides the porosity. The linear elastic FEM simulation also yields a substantially stiffer response than the MD simulation, which reveals that nonlinear elastic behavior contributes decisively to the anomalous compliance of nanoporous gold at small structure size. Graphical Abstract: